PIROLISIS MENGGUNAKAN SCREW SEBAGAI PRESSURE DROP DAN SIRIP PADA KONDENSOR - Pane, Erlanda A; Rahardjo, Stevanus Budi; Ismail, Ismail (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
The main factor that can determine the pyrolysis reaction is reactor type. However, the operational system of the pyrolysis reactor has a problem due to the low energy supply and low thermal conductivity of plastic. In addition, the particle agglomeration phenomenon occurs due to the presence of a thin layer due to the natural adhesive effect. This research made the development of the reactor design by the addition of a reactor section. The addition of a screw scrolls as a pressure drop system and fin parts on the condenser becomes the novelty. The aims of adding some sections are to reduce the particle agglomeration phenomenon and increase the quantity of syngas-pyrolysis oil from the system. The methodology is divided into design, manufacture, and pyrolysis experiments. This system can produce more pyrolysis oil compared to systems that use catalysts. The oil yield produced reached 88% at a target temperature of 450°C.